Chatalone : crowd chat application - How, Yi De (Nanyang Technological University, 2021)
When a person is faced with a challenge or requires help but there is no one you know that is available. You are faced with a dilemma to ask the nearest stranger for help. But nowadays, talking to strangers has become a challenge for many people. Most people are overly self-conscious, and fear being judged by others, hence lacking the courage to ask a stranger for help. Companies have created messaging applications that allow users to message other users that are nearby. By using these applications, people do not have to fear being judged as they do not need to see the stranger’s expressions face-to-face which allows the people who are afraid of approaching a stranger to be able to ask for their help. However, there is an issue of privacy. Messaging companies like WhatsApp had been under fire over privacy issues which may discourage people from using the messaging applications to ask for help worrying that their personal information and messages may be leaked via the internet. There are messaging applications that instead of sending messages through the internet, send messages through a peer-to-peer mesh network using Bluetooth. While these applications may be a solution, some may still require access to the internet which is unsure if they are storing personal information, and some are unavailable only existing on one mobile operating system. This project aims to develop a cross-platform mobile-based messaging application that will allow users to chat with other users anonymously in a local area, through a peer-to-peer mesh network, without requiring internet or mobile network coverage.